Attitude to the legacy of Thomas Aquinas in byzantine theology during the initial period of hesychastic discussions - Elga Kanaeva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2020)
This article studies the fi rst episode in the encounter of Eastern theologians with theology of Thomas Aquinas (as it was presented by papal legates) which took place in the 1330s. It shows that of the two Orthodox authors, Barlaam and St. Gregory Palamas, the former took a harshly negative position, whereas the latter was positive. Barlaam, Thomas, and Palamas had similar views on natural theology which they considered to be possible, but Barlaam did not share Thomas’s opinion about the possibility of building the “sacred doctrine” (doctrina sacra) as an Aristotelian science. The article discusses Barlaam’s critical arguments against Thomas. It demonstrates that, on the one hand, Barlaam did not know many important points of Thomas’s theology (the theory of subalternation, the use of names “by analogy”), but, on the other hand, he found a number of weak points in his opponent’s reasoning (the problem of uniqueness and causality in theology). It is concluded that Barlaam had no acquaintance with the original texts of Thomas but used their interpretation. In a dispute with Barlaam, Gregory Palamas fi rst defended the possibility of building dogmatic theology as a science; at this stage he was methodologically close to Thomas using his own syllogisms of the procession of the Holy Spirit, but during the dispute he reshaped his position. Although at this stage of the development of his system, his proposed “demostration above demostration» did not became a programme, but the beginning of developing a question about the relationship between the essence and energy in God marked not only introducing the problems of Hesychasm to the discussions, but also made up a new step in the search for a way of including the reason into the process of cognition of theological truths. The article also concludes that Barlaam succeeded in playing the role of a critic of his opponents’ systems, which furthered their development. However, he himself did not manage to create his own synthesis.